A Giant Invasive Papillary Breast Carcinoma : A Rare Case Report - Wibowo, Joko; Soewoto, Widyanti (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: Invasive papillary carcinoma represents a rare subtype of breast cancer, constituting about 0.5% of all invasive breast cancers and mainly occurring in postmenopausal women. Because most information comes from limited case reports and small retrospective analyses, awareness of this tumor remains low, posing challenges for clinical management. There are distinct pathological characteristics and biological behaviors seen in invasive papillary carcinoma, according to the research. One reason for its generally good prognosis is because it is seldom involved with lymph nodes and is classified as a luminal subtype. [1, 2]. Case Presentation: We report a rare case of Invasive Papillary Breast Carcinoma in a 48-year-old premenopausal woman who presented with a gradually enlarging, painless retroareolar mass in her right breast, persisting for four months. The patient previously underwent an incisional biopsy at another hospital, and the histopathology results showed invasive papillary breast carcinoma. The patient has undergone a chest CT-scan for diagnostic confirmation and surgical guidance. The patient underwent a right-sided modified radical mastectomy, and histopathological examination of the specimen confirmed the diagnosis of Invasive Papillary Carcinoma. Immunohistochemical analysis further validated this diagnosis. Conclusion: Although the treatment of Invasive Papillary Breast Carcinoma generally aligns with that of more common breast cancers, its protocol remains unclear due to the condition's rarity. We chose to present this Invasive Papillary Breast Carcinoma case because of the disease's uncommon nature, the severity of the symptoms, and the need for urgent intervention.